2012
DOI: 10.1007/s10695-012-9618-0
|View full text |Cite
|
Sign up to set email alerts
|

The switch of secondary sex determination in protandrous black porgy, Acanthopagrus schlegeli

Abstract: Hermaphrodites have both sexes during their life, including an initial primary sex determination and in later stage maintenance one of the sexual fates (secondary sex determination). Sex change (secondary sex determination) occurs in animals, but it is lost in amphibians through, mammals in vertebrates. Teleosts have various strategies and mechanisms of sex determination including genetic and environmental cues. However, the mechanisms by which the cues guide sex change are complicated in fish. This manuscript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 29 publications
1
25
0
1
Order By: Relevance
“…Many differentiated cells in other organs share a common bipotential progenitor, however, it is unclear whether the phenomenon of transdifferentiation between differentiated fates occurs naturally in other systems, or whether it is specific to gonadal cells. It could be an evolutionary remnant of the ability of some fish to switch sex in adult life [102] or of some vertebrates’ ability to function as ‘natural hermaphrodites’ by maintaining a gonad with seasonally expanding ovarian and testicular regions such as the mole and alligator [103,104]. It will be interesting to see how this plasticity of cell fate is related to the epigenetic landscape at the bipotential stage, and in Sertoli and granulosa cells during fetal and adult life.…”
Section: Discussionmentioning
confidence: 99%
“…Many differentiated cells in other organs share a common bipotential progenitor, however, it is unclear whether the phenomenon of transdifferentiation between differentiated fates occurs naturally in other systems, or whether it is specific to gonadal cells. It could be an evolutionary remnant of the ability of some fish to switch sex in adult life [102] or of some vertebrates’ ability to function as ‘natural hermaphrodites’ by maintaining a gonad with seasonally expanding ovarian and testicular regions such as the mole and alligator [103,104]. It will be interesting to see how this plasticity of cell fate is related to the epigenetic landscape at the bipotential stage, and in Sertoli and granulosa cells during fetal and adult life.…”
Section: Discussionmentioning
confidence: 99%
“…Most research has focussed on black porgy ( Acanthopagrus schlegeli , Sparidae), which reproduce as male for the first 2 years of life before roughly 50% of fish change sex to female [reviewed by Lee et al, 2001;Wu et al, 2010a;Wu and Chang, 2013]. Australian barramundi ( Lates calcarifer , Latidae) and gilthead seabream ( Sparus aurata , Sparidae) also sexually mature as male before becoming female at an older age and larger size [Guiguen et al, 1994;Liarte et al, 2007].…”
Section: Protandrymentioning
confidence: 99%
“…3 A). The reverse pattern is evident from numerous candidate gene studies in protandrous black porgy: male-related gene expression (e.g., dmrt1 , amh , amhr2 ) declines coincidentally with testis volume before expression profiles are increasingly feminised as the bisexual gonad becomes purely ovarian (e.g., cyp19a1a / b , foxl2 , wnt4 ) [reviewed by Wu and Chang, 2013]. Broadly speaking, the greatest shift in sex-specific gene expression occurs during mid-to-late sex change ( fig.…”
Section: Molecular Regulation Of Sex Change: Switches Triggers and mentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study on the ancestral reconstruction of sexual patterns in sparids revealed both gonochorism and hermaphroditism in almost every group of the family [31]. Therefore, there is a great potential for understanding the molecular mechanisms underlying gonochorism and hermaphroditism within Sparidae [31, 35]. To date, considerable effort to unravel the genes involved in sex determination, sex differentiation and sex change have been conducted mainly on the protandrous black porgy, Acanthopagrus schlegelii [3542].…”
Section: Introductionmentioning
confidence: 99%